ANALISIS YURIDIS TERHADAP PUTUSAN MK NOMOR 128/PUU XXIII/2025 : KONSTITUSIONALITAS RANGKAP JABATAN WAKIL MENTERI - Sakdi Sakdi; Moh. Siswanto; Imam Bustomi (Jurnal Yustitia, 2026)
The position of the Deputy Minister in Indonesia’s governmental system remains a constitutional and legal debate, as it is not explicitly mentioned in the 1945 Constitution of the Republic of Indonesia. Although regulated under Law Number 39 of 2008 concerning State Ministries, the regulation only prohibits Ministers from holding concurrent positions, without extending the same prohibition to Deputy Ministers. This regulatory gap creates legal uncertainty and potential conflicts of interest within the executive branch. This study aims to analyze the constitutional and legal status of the Deputy Minister and to examine the legal reasoning of the Constitutional Court in Decision Number 128/PUU-XXIII/2025 regarding the prohibition of dual positions for Deputy Ministers. The research employs a normative juridical methodwith statutory, conceptual, and case approaches. The legal materials consist of primary sources such as legislation and court rulings, secondary sources including books and legal journals, and tertiary sources such as legal dictionaries and encyclopedias. The findings reveal that the Deputy Minister holds an administrative position subordinate to the Minister, valid under positive law but without direct political responsibility to the President. The Constitutional Court ruled that allowing Deputy Ministers to hold multiple positions contradicts the principles of equality before the law and the general principles of good governance (AUPB). Consequently, the Court emphasized that the prohibition of concurrent positions must also apply to Deputy Ministers. This decision reinforces the principles of good governance, accountability, and constitutional morality among public officials to ensure a clean, transparent, and just government administration. Keywords: Constitutional Court, Deputy Minister, Dual Position Prohibition, Good Governance, Constitutionality